Hyperuricemia, Elevated Body Mass Index, Female Sex, and Albuminuria Increase the Probability of Elevated High-Sensitivity C-Reactive Protein: Results From the National Health and Nutrition Examination Survey 2015-2018 - Cristin D. W. Kaspar; Juan Lu (Frontiers Media S.A., 2021)
Importance: High uric acid (UA) is hypothesized to worsen kidney and cardiovascular disease morbidity via activation of systemic inflammation. Clinical trials of UA modification report reduction of the inflammatory marker high sensitivity C-reactive protein (hs-CRP) as an outcome measure, but studies have not demonstrated that hyperuricemia independently increases hs-CRP when adjusted for important confounders such as body mass index (BMI), sex, and age.Objective: To identify clinical risk factors for elevated hs-CRP, including but not limited to hyperuricemia, through a cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES) 2015-2018.Results: In the final multivariate logistic regression model, the exposure with the strongest effect on the odds of elevated hs-CRP was BMI in the fourth quartile, OR = 13.1 (95% CI 6.25-27.42), followed by female sex (OR = 4.9, 95% CI 2.92-8.34), hyperuricemia (OR = 2.2, 95% CI 1.36-3.45), urine albumin creatinine ratio (ACR; OR = 1.5, 95% CI 1.09-2.18), poor overall health (OR = 1.4, 95% CI 1.18-1.58), and interactions between hyperuricemia and sex (OR = 1.4, 95% CI 1.05-1.83), and between BMI and sex (OR = 1.2, 95% CI 1.03-1.47). Notably, chronic kidney disease (CKD) and CKD surrogates were not associated with hs-CRP despite urine ACR maintaining a significant independent effect.Conclusions: In this national population-based study, we demonstrated that hyperuricemia significantly increases the odds of elevated hs-CRP, independent from BMI, female sex, urine ACR, and overall health status. Further study is recommended to better understand the sex difference in this association and the role of albuminuria, but not CKD, in systemic inflammation.